Praktik Pengelolaan Dana Produktif dan Implikasinya terhadap Kesejahteraan Anak pada LKSA Sentosa Banjarmasin - Risky Mustika Wardani; Mochammad Arif Budiman (P3M Politeknik Negeri Banjarmasin, 2025)
This study aims to analyze the practices of productive fund management and their implications for child welfare at LKSA Sentosa Banjarmasin. The research employs a qualitative approach with a case study design to explore in depth how the institution manages productive assets as an alternative and sustainable funding source. Data were collected through in-depth interviews, direct observation, and documentation involving institutional managers and related stakeholders. The findings reveal that LKSA Sentosa has implemented productive fund management through several business units, including a guest house, shop-house rentals, and a multipurpose hall, which generate stable income to support institutional operations and child welfare programs. The management practices reflect a shift from donation-dependent financing toward a more sustainable and self-reliant financial model. Furthermore, the generated income contributes significantly to improving children’s welfare, particularly in fulfilling basic needs, supporting educational access, strengthening social protection, and facilitating spiritual and character development. These findings indicate that productive fund management not only enhances institutional financial sustainability but also creates broader social impacts on beneficiaries. This study contributes to the literature on social institution management by highlighting the potential of productive asset-based financing in strengthening child welfare within Islamic social institutions.